Doppler radar, satellites, and computer models : the science of weather forecasting - Fleisher, Paul. (Minneapolis : Lerner Publications, 2011)
Discusses the tools and techniques used by meteorologists to predict the weather, including doppler radar, satellite technology, and advanced computer models.
Gathering weather information -- Reading a weather map -- Making a prediction -- Predicting climate change.
Includes bibliographical references (p. 45-46) and index.
5.0
3-6
3-6
Keywords: Weather forecasting -- Juvenile literature; Weather forecasting; Weather forecasting